Strategy to Increase Competitiveness of East Nusa Tenggara Local Products in Supporting Sustainable Tourism - Rahmawati Rahmawati; Abuzar Khpalwak Zazai (Tinta Emas Publisher, 2025)
This study aims to explore and analyze strategies for enhancing the competitiveness of local products in East Nusa Tenggara (NTT) through an approach that emphasizes their role in supporting sustainable tourism. Local products are regarded not only as vital economic assets but also as instruments for cultural preservation and the promotion of regional identity. A quantitative descriptive method is employed, integrating surveys of local business actors, analysis of secondary data related to trade policies and product development, and in-depth interviews with key stakeholders, including representatives from the Kupang City Trade Office. The findings reveal that several critical factors—such as improving product quality through innovation, adopting branding strategies rooted in local wisdom, and leveraging digital technology for marketing—significantly contribute to enhancing product competitiveness. These factors add value to NTT’s local products in both domestic and international markets. Moreover, strong collaboration among the government, business actors, and the community serves as a foundational pillar for the effective implementation of these strategies. The study also underscores the importance of continuous capacity-building programs for local entrepreneurs, product certification in accordance with national and international standards, and the integration of local products into tourism packages. These efforts not only boost the appeal of NTT's tourism sector but also positively impact the local economy by empowering communities. In the long term, the proposed strategies are expected to foster an inclusive and sustainable business ecosystem aligned with the Sustainable Development Goals (SDGs).